Development And Feasibility Of A Self-Report Checklist For TAND-SQ In Children With TSC Neonatal Botulism: A Systematic Review (The Review of Diabetic Studies, 2025)
Background:Tuberous sclerosis complex (TSC) is a neurogenetic disorder frequently associated with neuropsychiatric manifestations, collectively termed TSC-associated neuropsychiatric disorders (TAND). Early identification and management are hindered by symptom heterogeneity and service gaps. Parallelly, rare pediatric conditions like neonatal botulism demand timely detection and standardized care.Objectives:This review aimed to synthesize recent empirical evidence on the development, validation, and application of self-report tools for TAND, and to contextualize these advances alongside clinical insights from neonatal and infant botulism studies.Methods:A systematic review was conducted following PRISMA 2020 guidelines. Studies included those focusing on TAND self-report assessment tools (e.g., TAND-SQ) or clinical/epidemiological research on neonatal botulism. Ten peer-reviewed articles published from 2015–2025 were included after screening multiple databases.Results:Self-report tools for TAND, particularly the TAND-SQ, demonstrated high feasibility, reliability, and validity across diverse populations. Structured screening increased detection of psychiatric comorbidities and informed individualized interventions. Early epilepsy severity in TSC predicted developmental delays. For neonatal botulism, standardized early interventions were associated with better clinical outcomes.Conclusions:Validated self-report instruments such as the TAND-SQ offer scalable solutions for routine TAND assessment, bridging gaps in care. The clinical parallels with neonatal botulism underscore the broader imperative for early, structured screening in rare pediatric neurodevelopmental disorders.